Clinical manifestations and frequency of hypocalcemia in 22q11.2 deletion syndrome. Issue 6 (26th November 2015) - Fujii, Sachiko; Nakanishi, Toshio
Abstract: Background: This study investigated the evolution of hypocalcemia with age and its associated risk factors in patients with 22q11.2 deletion syndrome (22qDS) and congenital heart defects. Method: A retrospective review of the medical records of 16 22qDS patients (nine female, seven male; age range, 20.5–43 years) was performed. The frequency of hypocalcemia, as well as the clinical course of the disease and the presence of other phenotypes, were investigated. Results: Ten of the 16 patients (62.5%) had a history of hypocalcemia. Among the 10 patients, the first onset of hypocalcemia occurred in the following developmental periods: neonatal stage, n = 1; early childhood, n = 3; late childhood, n = 2; adolescence, n = 2; and adulthood, n = 2. Neonatal hypocalcemia was observed in one patient, but it was transient. Two patients had sustained hypocalcemia after cardiac surgery. Hypocalcemia in one patient was transient following cardiac surgery, but it recurred during early adulthood. One patient developed hypocalcemia at 43 years of age. Thymus defect tended to be correlated with history of hypocalcemia ( P  = 0.09). This condition was often transient (60%) and was triggered by physical stress, such as intracardiac surgery. Conclusion: In 22qDS patients, hypocalcemia was often mild and transient during childhood, but it may recur in adulthood. Routine clinical measurement of serum calcium is recommended, particularly in 22qDS patients with thymic defect or in patients who are under physical stress.